PSYCHOLOGICAL ASPECTS OF THE QUALITY OF LIFE OF MEN WITH ORGASMIC DYSFUNCTION - Trishch, Volodymyr (Eastern Ukrainian Medical Journal, 2026)
Aim: to analyze the quality of life and aspects of mental health in men with orgasmic dysfunction, in particular, the development of anxiety and depressive disorders. Materials and Methods. An observed case-control study was conducted. The main group consisted of 20 men with orgasmic dysfunction, and the control group consisted of 200 practically healthy men. Standard questionnaires were used to assess quality of life and psychological characteristics: Quality of Life Enjoyment and Satisfaction Questionnaire – Short Form (Q-LES-Q-SF), Oxford Happiness Inventory (OHI), Hospital Anxiety and Depression Scale (HADS). Results. It was found that orgasmic dysfunction in men is accompanied by a significant decrease in quality of life (by 40.0%), the main components of which are dissatisfaction with sexual life (95.0% of respondents), mood (55.0%), leisure time (50.0%) and general physical condition (25.0%). Men with orgasmic dysfunction are characterized by an extremely low level of integral happiness index OHI (13.8% [10.3–17.8] out of a maximum of 100%) against the background of 100% prevalence of severe depression and the presence of mild in 35.0% and moderate anxiety in 65.0%. It was proved that in case of orgasmic dysfunction in men, there is a negative strong correlation (rs= -0.85, p˂0.05) between the integral happiness index OHI and anxiety and a negative moderate correlation (rs= -0.52, p˂0.05) between the integral happiness index OHI and depression. Conclusions. In the management of orgasmic dysfunction in men, psychological assistance aimed at correcting depression and anxiety and improving the quality of life of patients should be an obligatory component.